2017
DOI: 10.1111/jocn.13800
|View full text |Cite
|
Sign up to set email alerts
|

Post‐traumatic stress disorder in the perinatal period: A concept analysis

Abstract: Aims and objectives To report an analysis of the concept of perinatal posttraumatic stress disorder (PPTSD). Background Prevalence of PPTSD is rising in the United States, with 9% of the U.S. perinatal population diagnosed with the disorder and an additional 18% being at risk for the condition. Left untreated, adverse maternal-child outcomes result in increased morbidity, mortality, and healthcare costs. Design Concept analysis via Walker and Avant’s approach. Methods The databases Cumulative Index to Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 68 publications
2
29
0
Order By: Relevance
“…It is already known that there are lower birth rates among those who have experienced a traumatic birth (Gottvall and Waldenström, 2002), and higher rates of elective cesarean section among those women who do have more children (Kottmel et al, 2012). Vignato et al (2017) also found that experiencing PTSD from a previous birth may lead to women accessing less antenatal care in subsequent pregnancies. Little is known about other choices women make during pregnancy and birth, when they have previously experienced a traumatic birth, or what supports or hinders women in making these choices.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is already known that there are lower birth rates among those who have experienced a traumatic birth (Gottvall and Waldenström, 2002), and higher rates of elective cesarean section among those women who do have more children (Kottmel et al, 2012). Vignato et al (2017) also found that experiencing PTSD from a previous birth may lead to women accessing less antenatal care in subsequent pregnancies. Little is known about other choices women make during pregnancy and birth, when they have previously experienced a traumatic birth, or what supports or hinders women in making these choices.…”
Section: Introductionmentioning
confidence: 97%
“…If childbirth-related chronic-PTSD and delayed-PTSD is left untreated, it can continue to affect women for many years (Forssén, 2012). Consequences of traumatic birth include enduring mental health problems (Beck, 2004b; Forssén, 2012; Vignato et al, 2017), compromised maternal infant relationships (Nicholls and Ayers, 2007; Vignato et al, 2017) leading to adverse child cognitive development (Vignato et al, 2017), lower rates of breastfeeding (Vignato et al, 2017), poorer quality marital relationships (Ayers et al, 2006) and a negative impact on sex life (Vignato et al, 2017), concomitant depression in partners (Nicholls and Ayers, 2007), and can present a challenge to future reproductive decisions, with a higher proportion of women who have experienced a traumatic birth choosing not to become pregnant again (Fenech and Thomson, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, stress or GC exposure has harmful effects on reproduction, such as fetal growth restriction, infertility, miscarriage, stillbirth, preterm birth, low birth weight, and postnatal hypertension 9‐16 . Post‐traumatic stress disorder (PTSD), a serious psychological condition that occurs following exposure to a traumatic event, has a negative impact on female reproduction 17,18 . A traumatic event can stimulate the release of GCs from adrenal cortex into the bloodstream by initiating hypothalamic‐pituitary‐adrenal axis 19 .…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] Post-traumatic stress disorder (PTSD), a serious psychological condition that occurs following exposure to a traumatic event, has a negative impact on female reproduction. 17,18 A traumatic event can stimulate the release of GCs from adrenal cortex into the bloodstream by initiating hypothalamic-pituitary-adrenal axis. 19 Elevated GCs levels are often used as biomarkers for stress and have adverse effects on pregnancy in hypercortisolism.…”
mentioning
confidence: 99%
“…Perinatal PTSD is defined as a disorder occurring after a traumatic experience, diagnosed any time from conception to 6 months postpartum, lasting longer than 1 month, and leading to specific negative diagnostic maternal symptoms and poor maternal-infant outcomes (Vignato, Georges, Bush, & Connelly, 2017). A concept analysis indicated antecedents or risk factors include trauma (perinatal complications and abuse [child, IPV, sexual]), previous psychiatric history, and postpartum depression (Vignato et al, 2017). If left untreated, perinatal PTSD has the potential to increase healthcare costs and adverse health disparities from decreased maternal child bonding, prematurity/low birth weight, poor prenatal care, risky behaviors (e.g.…”
Section: Introductionmentioning
confidence: 99%